Reading Scripture in Latin America: An Evangelical Perspective From the Grassroots - Grajales, Sergio Zapata (Journal for the study of the New Testament, 2024)
This essay illustrates the practices, methods, and commitments of New Testament interpreters in Latin America. The first section provides a theoretical framework and the second section provides an example of the kind of interpretation Latin American scholars practice, focused on the Gospel of John, specifically John 9. The main thesis of the essay is that New Testament interpreters in Latin America focus both on hearing God and practising the mission of God to all people. There are particular methods that best serve this interpretive purpose. Such methods focus on the text and on understanding history for the sake of engagement with the text. The role of the reader is not so much to define beforehand what a text says or to find passages that serve a particular purpose, but to engage with the many contexts that make a text what it is, with the aim to hear the God who is behind the text.